TINJAUAN FIQHIYYAH TERHADAP PENGULANGAN IJAB DAN KABUL DALAM AKAD PERKAWINAN DI KECAMATAN DOLOK - Sawaluddin Siregar; Misbah Mrd (I’tiqadiah: Jurnal Hukum dan Ilmu-ilmu Kesyariahan, 2024)
This research will analyze according to fiqhiyyah method the repetition of ijab and kabul in marriage. The repetition happened because of a redaction error in the pronunciation of ijab and Kabul. In the rules of fiqhiyyah I'imal al kalam aula min ihmalili (meaning a speech is better than ignoring it). As for the type of this research, it is an empirical legal research that analyzes problems by combining legal materials (which are secondary data) with primary data obtained in the field. As for the results of the research that the repetition occurred in Dolok District due to the repetition of the contract which is clear if linked to the rules of fiqhiyyah it includes wasting a speech, but the repetition is caused to strengthen the first ijab and kabul so that he does not ignore the first ijab and Kabul.